FORENSIC ISSUES OF CATEGORIZING CONSTRUCTION PROJECTS AS PERMANENT STRUCTURES: METHODOLOGICAL GUIDELINES FOR FORENSIC EXAMINERS - Andrei R. Chudievich; Andrei Yu. Butyrin; Dar'ya V. Khamidova (Теория и практика судебной экспертизы, 2018)
The article addresses the issue of subsuming construction projects under the category of permanent (non-permanent) structures. The authors offer detailed criteria for successful resolution of this issue, and present the appropriate course of inquiry for this line of forensic engineering investigation. Special emphasis is placed on the resolution of complex forensic situations. The paper incorporates a systematic overview of primary and secondary indicators for identifying buildings, structures and facilities as permanent or non-permanent. Recommendations draw on extensive regulatory resources, as well as generalization, systematization and analysis of current forensic practices, and are illustrated with specific examples.